Croton gratissimus leaf extracts inhibit cancer cell growth by inducing caspase 3/7 activation with additional anti-inflammatory and antioxidant activities - Mfotie Njoya, Emmanuel (BMC Complement Altern Med, 2018)
BACKGROUND: Croton species (Euphorbiaceae) are distributed in different parts of the world, and are used in traditional medicine to treat various ailments including cancer, inflammation, parasitic infections and oxidative stress related diseases. The present study aimed to evaluate the antioxidant, anti-inflammatory and cytotoxic properties of different extracts from three Croton species. METHODS: Acetone, ethanol and water leaf extracts from C. gratissimus, C. pseudopulchellus, and C. sylvaticus were tested for their free radical scavenging activity. Anti-inflammatory activity was determined via the nitric oxide (NO) inhibitory assay on lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages, and the 15-lipoxygenase inhibitory assay using the ferrous oxidation-xylenol orange assay. The cytotoxicity of the extracts was determined on four cancerous cell lines (A549, Caco-2, HeLa, MCF-7), and a non-cancerous African green monkey (Vero) kidney cells using the tetrazolium-based colorimetric (MTT) assay. The potential mechanism of action of the active extracts was explored by quantifying the caspase-3/− 7 activity with the Caspase-Glo® 3/7 assay kit (Promega). RESULTS: The acetone and ethanol leaf extracts of C. pseudopulchellus and C. sylvaticus were highly cytotoxic to the non-cancerous cells with LC(50) varying between 7.86 and 48.19 μg/mL. In contrast, the acetone and ethanol extracts of C. gratissimus were less cytotoxic to non-cancerous cells and more selective with LC(50) varying between 152.30 and 462.88 μg/mL, and selectivity index (SI) ranging between 1.56 and 11.64. Regarding the anti-inflammatory activity, the acetone leaf extract of C. pseudopulchellus had the highest NO inhibitory potency with an IC(50) of 34.64 μg/mL, while the ethanol leaf extract of the same plant was very active against 15-lipoxygenase with an IC(50) of 0.57 μg/mL. A linear correlation (r<0.5) was found between phytochemical contents, antioxidant, anti-inflammatory and cytotoxic activities of active extracts. These extracts induced differentially the activation of caspases − 3 and − 7 enzymes in all the four cancerous cells with the highest induction (1.83-fold change) obtained on HeLa cells with the acetone leaf extract of C. gratissimus. CONCLUSION: Based on their selective toxicity, good antioxidant and anti-inflammatory activities, the acetone and ethanol leaf extracts of C. gratissimus represent promising alternative sources of compounds against cancer and other oxidative stress related diseases. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12906-018-2372-9) contains supplementary material, which is available to authorized users.